Enkripsi Database Sekolah SMK Pembangunan Dengan Algoritma IDEA - Devlin Iskandar Saragih; Paska Marto Hasugian (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2021)
One of the algorithms in cryptography that can be used for school database security is the IDEA (International Data Encryption Algorithm) algorithm. The IDEA algorithm is one of the cryptographic algorithms that has various applications in secure data transmission in the scope of networks and distributed measurement systems. Encryption results appear in the form of a notepad. The Open data button is used to find data that will be used for the encryption process. The key checklist is used to input the key length that will be used for the encryption decryption security process. The system displays the IDEA Cryptographic key, can use the IDEA Cryptographic key, the encryption and decryption change process is clearly visible. Encryption is done on the SMK Pembangunan school database with IDEA algorithm and designing the student database encryption application based on the name of the SMK Pembangunan using Visual Basic programming language.